Efficacy and safety of belimumab versus rituximab for refractory immune thrombocytopenia in patients with connective tissue disease - Min Wang; Yudong Liu; Tong Li; Xuan Zhang; Ying Jiang; Xiaoxia Zuo; Xiangning Yuan (Lupus Science and Medicine)
Objectives Immune thrombocytopenia (ITP) is a haematological manifestation secondary to connective tissue disease (CTD). Many patients with CTD–ITP are refractory to glucocorticoids (GCs) plus immunosuppressant agents (ISAs); rituximab (RTX) is the recommended second-line therapy. Belimumab (BLM) shows efficacy against CTD. We compared the efficacy and safety of RTX and BLM.Methods Data of patients with CTD–ITP refractory to GCs plus ISAs administered were collected. The data of 11 patients with refractory CTD–ITP who received BLM were compared with those of 15 patients treated with RTX.Results At week 2, BLM resulted in a better overall response (OR) than RTX (72.7% vs 26.7%, p=0.045). The OR rate was 60.0% (9/15), 66.7% (10/15) and 73.3% (11/15) at week 4, 8 and 12, respectively, in the RTX group. It remained at 72.7% (8/11) during week 4–12 in the BLM group. Excluding the data of three deceased patients, the OR rate dropped at week 24 in both groups (RTX vs BLM, 61.5% (8/13) vs 70.0% (7/10), p=1.000). At week 24, four patients with OR in both groups successfully withdrew GCs to <15 mg prednisone (RTX vs BLM, 40% (4/10) vs 66.7% (4/6), p=0.608). The serum C3 level did not significantly change, whereas the serum immunoglobulin G level significantly decreased at week 4, 8 and 12 in both groups. There were three patients with serious adverse effects who died of severe pneumonia during weeks 12–24.Conclusions BLM may be a safe and effective alternative to RTX for CTD–ITP refractory to GCs plus ISAs.